Estetika Dalam Tradisi Sakral: Telaah Filosofis Atas Praktik Ritual Di Desa Gulingan Badung - Darmawan, I Putu Ariyasa (Jurnal Penelitian Agama Hindu, 2025)
Art in Balinese Hindu society functions not merely as an aesthetic expression, but as an integral component of ritual practices that reflect cosmological and spiritual values. Gulingan Village in Badung serves as a significant locus for the preservation and transformation of sacred art, yet philosophical studies that position art as a medium of spiritual transcendence within Hindu aesthetics remain limited, particularly within customary communities. This study aims to explore in depth the roles and meanings of art in the religious practices of the Gulingan community, emphasizing the symbolic, spiritual, and social dimensions embedded in sacred artistic expressions. The research employs a qualitative method with a phenomenological approach, utilizing in-depth interviews, participatory observation, and documentation of artistic practices. The findings reveal that art in Gulingan is perceived as an act of devotion and a medium for uniting humans, nature, and the divine, as embodied in the Hindu aesthetic principles of Satyam, Śivam, and Sundaram. Art serves a symbolic and pedagogical function as a sacred language that reinforces spiritual awareness and cultural identity. Community participation in transmitting these artistic traditions also fosters a space for dialogue between tradition and modernity. In conclusion, art in Gulingan is not merely an aesthetic expression but a cosmological and transformative medium that binds spiritual, social, and ecological relationships into a unified value system. Art plays an active role in fostering social cohesion, maintaining spiritual continuity, and articulating the values of Tri Hita Karana in the daily lives of Gulingan communities. This study contributes to the development of Hindu aesthetic discourse by highlighting how sacred art functions as a living philosophical praxis within a local community context, thereby enriching the field of community-based sacred art studies.